Staging Holiness: The Case of Hospitaller Rhodes (ca. 1309-1522) - Zoitou, Sofia (Mediterranean Art Histories, 2020)
In Staging Holiness: The Case of Hospitaller Rhodes (ca. 1309-1522) Sofia Zoitou offers a study of the history of relic collections, devotional rituals, and sites invested with special meaning on Rhodes, during a time when the island became one of the most frequented ports of call for ships carrying pilgrims from Venice to the Holy Land. Scrutinizing late medieval travel reports by pilgrims from all over Europe along with extant historical, archaeological, visual, and material evidence, Sofia Zoitou traces the various forms of the Rhodian cultic sites' evolution and perception, ultimately considered as an overall artistic strategy for the staging of the sacred. Readership: All interested in the history of cultic phenomena in Hospitaller Rhodes and their material aspects, in late medieval pilgrimage to the Holy Land, and in intercultural connections in the eastern Mediterranean.